An environmental input-output model for Ireland - Joe ODoherty; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
This paper is presented in two parts. The first part demonstrates an environmental input-output model for Ireland for the year 2000. Selected emissions are given a monetary value on the basis of benefit-transfer. This modelling procedure reveals that certain sectors pollute more than others - even when normalised by the sectoral value added. Mining, agriculture, metal production and construction stand out as the dirtiest industries. On average, however, each sector adds more value than it does environmental damage. The second part uses the results of this input-output model - as well as historical data - to forecast emissions, waste and water use out to 2020. The growth in emissions of fluorinated gases and carbon monoxide and the growth of hazardous industrial waste exceed economic growth. Other emissions grow more slowly than the economy. Emissions of acid rain gases (SO2, NOx and NH3) will decrease, even if the economy grows rapidly.
Keywords: 330; Umweltbelastung; Prognose; Input-Output; Irland